2022
DOI: 10.1161/circresaha.122.320877
|View full text |Cite
|
Sign up to set email alerts
|

Interleukin-6 Predicts Carotid Plaque Severity, Vulnerability, and Progression

Abstract: BACKGROUND: IL-6 (interleukin-6) has important roles in atherosclerosis pathophysiology. To determine if anti-IL-6 therapy warrants evaluation as an adjuvant stroke prevention strategy in patients with carotid atherosclerosis, we tested whether circulating IL-6 levels predict carotid plaque severity, vulnerability, and progression in the prospective population-based CHS (Cardiovascular Health Study). METHODS: Duplex carotid ultrasound was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(23 citation statements)
references
References 64 publications
0
16
0
1
Order By: Relevance
“…8,13 Some previous clinical evidence revealed that the elevation of IL-6 is associated with the severity, vulnerability, and progression of carotid atherosclerotic plaques. 14,15 Genetic studies confirmed the causal relationship between IL-6 signaling and atherosclerotic disease. 16 Basic research has found that IL-6 plays an important role in initiating and maintaining atherosclerotic plaque development and plaque destabilization in many ways, including the proliferation and migration of smooth muscle cells and the recruitment and activation of the inflammatory mediators.…”
Section: Discussionmentioning
confidence: 86%
See 1 more Smart Citation
“…8,13 Some previous clinical evidence revealed that the elevation of IL-6 is associated with the severity, vulnerability, and progression of carotid atherosclerotic plaques. 14,15 Genetic studies confirmed the causal relationship between IL-6 signaling and atherosclerotic disease. 16 Basic research has found that IL-6 plays an important role in initiating and maintaining atherosclerotic plaque development and plaque destabilization in many ways, including the proliferation and migration of smooth muscle cells and the recruitment and activation of the inflammatory mediators.…”
Section: Discussionmentioning
confidence: 86%
“…13,17 In addition, a recent study demonstrated that the proatherothrombotic effect from cardiovascular risk factors at least in part by accelerating IL-6-mediated arterial inflammation and remodeling. 15 Furthermore, the atherosclerosis-protective effect of some new anti-inflammatory drugs is mediated by reducing circulating IL-6 levels. 15 Together with the present study, our findings supported the assumption that IL-6 is linked to the progression of atherosclerosis.…”
Section: Discussionmentioning
confidence: 99%
“…The findings in the present study probably reflect the results of younger patients preferring diets that raise TG values. Although symptomatic carotid stenosis was also an independent risk factor for the progression in this study, the finding may reflect the importance of local factors such as inflammation [ 10 ], which cannot be shown by degree of stenosis and SIR of plaques.…”
Section: Discussionmentioning
confidence: 91%
“…У 29,2% больных наблюдалась уязвимость бляшки, у 34,0% -прогрессирование бляшки. Уровень IL-6 коррелировал с размером бляшек и их уязвимостью [отношение шансов (ОШ) 1,21; 95% доверительный интервал (ДИ) 1,05-1,40; p=7,4×10 -3 ; E-значение 1,71] и прогрессированием (ОШ 1,44; 95% ДИ 1,23-1,69) [32].…”
Section: исследования посвященные роли Il-6 при атеросклерозе и ибсunclassified